Childhood Vaccinations and Associated Factors in 35 Sub-Saharan African Countries: Secondary Analysis of Demographic and Health Surveys Data from 358 949 Under-5 Children - Michael Ekholuenetale PhD; Victor A. Ochagu MSc; Olayinka Stephen Ilesanmi PhD; Okikiolu Badejo PhD; Amit Arora PhD (Global Pediatric Health)
Objective . We examined childhood vaccinations coverage and its associated factors in sub-Saharan Africa (SSA) countries. Methods . We used demographic and health surveys (DHSs) data collected between 2008 and 2022 from 35 SSA countries. A sample of 358 949 under-5 children was analyzed. Percentage and multivariable binary logistic regression analyses were conducted. A 5% significance level was set. Results . Rwanda (7461/8092; 92.2%), Burundi (10 792/13 192; 81.8%), Gambia (6548/8362; 78.3%), Kenya (14 570/19 530; 74.6%), and Burkina Faso (8739/12 343; 70.8%) had the leading coverage of under-5 children who received all basic vaccinations in the first year of life. For every unit increase in the age of a child, there was 72% increase in the odds of vaccination. Children from older mothers had higher odds of vaccination, when compared with children with mothers aged 15 to 19 years. There was a 6% reduction in the odds of vaccination among children from rural residence, when compared with their urban counterparts. Children with educated mothers had over two times higher odds of vaccination, when compared with those from mothers with no formal education. Children from rich households had higher odds of vaccination, when compared with children from poorest household. There was a 13% increase in the odds of vaccination among children covered by health insurance, when compared with those not covered by health insurance. Conclusion . Vaccination uptake for children under-5 in SSA was found to be sub-optimal and associated with several factors. A health educational intervention for pregnant women could potentially increase the uptake of vaccines among children.